17. Geology of the Southeast Missouri Lead District - Frank G. Snyder; Paul E. Gerdemann (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
The Southeast Missouri lead district, located about 70 miles south of St. Louis, embraces four important sub-districts and several minor ones. The important sub-districts, in order of discovery, are Mine La Motte, the Old Lead Belt, Indian Creek, and the Viburnum Lead Belt. Descriptions that follow are of geology and ore deposits of the Old Lead Belt. The ore deposits are stratiform in character and are localized in a narrow carbonate bar and algal reef environment on the flanks of exposed Precambrian of the St. Francois Mountains. Ore structures include a variety of primary depositional features such as pinchout zones, disconformities, ridge structures, reefs, and submarine gravity slides. Faulting, prior to and during ore deposition, "prepared" the host rock and strongly fractured areas are mineralized much more intensively and extensively than unfractured parts of the same sedimentary structures. The deposits are epigenetic in character. Mineralization is believed to have occurred at the time that post-lower Ordovician faulting took place. The mineralizing solutions are believed to be concentrated brines from adjacent basins that moved out of the basins during faulting, uplift, and erosion of the St. Francois positive area.